Lead like it matters ... because it does : practical leadership tools to inspire and engage your people and create great results! - Bahar Hewertson, Roxi (McGraw-Hill Education, 2015)
Whether you're running a large global firm or a small project team, it's the way you communicate and connect to other people that can make or break your success. The secret, according to Roxi Bahar Hewertson, is to make those connections count, to leverage your skills and play on your strengths, to lead like it matters--because it does. A virtual crash course in leadership, this book combines three decades of experience and research of the author's work at Cornell to create the definitive workbook. You will learn how to: assess your leadership style and skill set and make adjustments; create constructive dialogues including "managing up" and delegation; cut wasteful meetings out of your life and lead productive ones; address common interpersonal conflicts, quickly and gracefully; increase productivity, team effectiveness, and accountability; lead change initiatives that aren't dead on arrival, but ready for takeoff. --